MANAJEMEN PENGELOLAAN ZAKAT PRODUKTIF DALAM PERSPEKTIF BANK ISLAM - Agus Riyadi (IQTISHADIA, 2014)
Tulisan ini menganalisis tentang peluang pengelolaan zakat melalui bank syariah. Zakat produktif disadari memiliki peranan penting dalam  mengentaskan kemiskinan  dari pada zakat konsumtif. Argument tulisan ini adalah bahwa zakat produtif akan lebih efektij jika dikelola oleh bank syariah. Sebagai institusi berbasis Islam, bank syariah bisa mengelola dana zakat dengan produk bank yang bebas riba. Lembaga dan organisasi perbankan syariah yang sehat  akan mampu mengelola  zakat secara professional. Proses pengelolaan  zakat produktif  bisa dilakukan dengan tiga cara: penerima  zakat menjadi kreditur dan debitur  sekaligus; transaksi dicatat dalam sistem bagi hasil; zakat diserahkan secara penuh.Kata Kunci: Menejemen, Zakat, Perbankan.MANAGEMENT  OF   PRODUCTIVE ZAKAT  IN   THE PERSPECTIVE OF ISLAMIC BANKING. This article analyzes the probability of zakat management by sharia banking. Productive Zakat considered having  a big  role in alleviating poverty than consumptive zakat. This article argues that it will be more effective if administered by Islam banking. Islam banking as an economic missionary institution can manage  productive  zakat through banking products free of usury. Moreover, a good organization and balance of Islamic banking makes it potential to manage zakat professionally. The management process of productive zakat  can be done by three alternatives; the recipient of zakat at the same time serves as creditor as well as debtor, creditor clients are included in the transaction of profit share, or that the zakat of debtor under the bank assistance is fully given.Keywords: Management, Zakat, Banking.